System of Zakat and Ushr – A Paradigm Shift after Eighteenth Amendment to the Constitution of Pakistan - Samra, Umbreen; Muhammad Saad Siddiqui (Journal of Islamic Thought and Civilization, 2021)
Zakat and Ushr are important instruments of the Islamic fiscal system. It is an obligatory practice of Islam aiming to help the society and give the deprived ones a better life and opportunities. The fundamentals of the Zakat and Ushr system are clearly defined by Shariah however, its collection and distribution is the responsibility of the state. In this regard, Zakat and Ushr Ordinance 1980 was implemented in Pakistan. The 18th Constitutional Amendment was notified in the Gazette of Pakistan on April 20, 2010. This amendment has redefined the structural contours of the state through a paradigm shift from a heavily centralized to a predominantly decentralized federation. In this regard ministry of Zakat and Ushr was devolved at the federal level and powers were given to provinces to make legislations regarding the subject. After this change provinces made the respective legislations for Zakat and Ushr. In this article, this provincial legislation is reviewed to find out their harmony with the Income Tax Law and practical steps are suggested to achieve the very purpose of these legislations. These steps will increase the collection of Zakat and Ushr that would be helpful to alleviate the poverty and overcome the financial problems of our masses predominantly from agricultural areas of Pakistan. This paper aims to discuss the role of zakat and Ushr as a mechanism for poverty eradication. For this article, qualitative research methodology is used. The content analysis method is adopted for comparison, quantify and analyze the data. Available data on the subject, both in Shariah and conventional law, has been analyzed in detail. Keywords: Zakat; Ushr, poverty, agricultural areas, constitution, decentralized federation, Income tax Law